induction in oil palm Elaeis guineensis for renewal (Arecales: Arecaceae) through herbicide mixtures (UNED Research Journal, 2016)
Oil palm, Elaeis guineensis Jacq, is one of the crops with the greater development and expansion at the commercial level, thanks to its high productivity of oilseed and low maintenance costs. The expansion of oil palm is of utmost importance for the agricultural sector and many small and medium producers generate resources that sustain poor rural areas. I evaluated the effect of senescence on palm used for renovation, with various herbicides and mixtures, in Río Claro, Costa Rica. The palms were injected mixtures of Glyphosate (30-40 mL), methyl metsulfuron (10-15 mL), Glyphosate (30 mL) with Plicoran (20 mL), Glyfosate 45 mL, methyl metsulfuron (30 mL), plicloran (40 ml) and MSMA (75 ml). All were mixed with water to a volume of 200 mL and compared with 150 mL of MSMA. The percentage of dry leaves was evaluated using scales of 0, 25, 50, 75 and 100% at 8, 22, 55 and 105 days after application. The experimental design was a randomized complete block with eight treatments and four replications. It was found that the herbicide MSMA had a greater affect at 8 and 22 days compared to all other treatments. However, it had similar effect as mixtures and glyphosate at 55 and 105 daa. On the other hand, the palms had tolerance to Metsulfuron methyl that inhibits the acetolactase synthase enzyme and to Plicoram that affects cell growth at the doses tested. Mixtures with water can reduce up to 50% the MSMA dose in plant death.
Keywords: Oil palm; removal; reseeding; inhibitors; MSMA